ASME 2011 World Conference on Innovative Virtual Reality 2011
DOI: 10.1115/winvr2011-5548
|View full text |Cite
|
Sign up to set email alerts
|

Design of Warning Delivery Strategies in Advanced Rider Assistance Systems

Abstract: European statistics show that motorbikes road accidents are extremely high and the reduction of such accidents is one of the main concern for the European community. Advanced Driver Assistance Systems are safety electronic systems used to assist the driver in avoiding risks and road accidents, by means of warnings sent before the situation becomes critical. The use of such systems in motorcycle context is currently lacking due to numerous variables that it is necessary to consider for making sure the riding. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This reflects the findings of other PTW simulator studies that examined combinations of sensory cues to issue a warning. In general, these studies report that multi-sensory warnings have the highest acceptance and result in objectively better rider performance in terms of reaction time (Valtolina et al 2011). One study examined the effectiveness of different types of auditory warning in a simulator setting and reported that warnings that use non-emotional sounds improved performance in hazard situations and led to speed reduction and to a safer gaze behavior (Di Stasi et al 2010).…”
Section: Human Machine Interface and Rider Acceptability Of Assistancmentioning
confidence: 99%
“…This reflects the findings of other PTW simulator studies that examined combinations of sensory cues to issue a warning. In general, these studies report that multi-sensory warnings have the highest acceptance and result in objectively better rider performance in terms of reaction time (Valtolina et al 2011). One study examined the effectiveness of different types of auditory warning in a simulator setting and reported that warnings that use non-emotional sounds improved performance in hazard situations and led to speed reduction and to a safer gaze behavior (Di Stasi et al 2010).…”
Section: Human Machine Interface and Rider Acceptability Of Assistancmentioning
confidence: 99%
“…In [21], researchers presented the experimental results on comfort and safety aspects of two advanced rider assistance systems: the Front Collision Warning (FCW) and the Lane Change Support (LCS). They used three different machine learning models (Hidden Markov Models, Support Vector Machines and Artificial Neural Networks) in order to get the riders' behavior patterns according to the reaction time needed to avoid front collisions.…”
Section: Improving the Motorcyclist Safetymentioning
confidence: 99%
“…A deep-belief network (DBN) [21] is defined as a stack of restricted Boltzmann machines (RBM), in which each RBM layer communicates with both the previous and subsequent layers. The nodes of any single layer don't communicate with each other laterally.…”
Section: Deep Learningmentioning
confidence: 99%
“…There are only a few ARAS that are currently commercially available; most systems are still at the experimental or developmental stage. Examples of systems at an experimental stage include intersection support [10], intelligent curve warning system [11], lane keeping and lane changing support [12,13], collision warning system [13] and autonomous braking [14,15].…”
Section: Current State-of-the-art Against Crash Typesmentioning
confidence: 99%